1999
DOI: 10.1103/physrevb.59.r725
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of holes and suppression of antiferromagnetic order inLa2xSrxet al.

Abstract: We have measured the static magnetic susceptibility and the resistivity of Zn (0рzр0.25) and Sr (0рx р0.03) doped La 2 CuO 4 . Our data clearly show that Zn impurities lead to an increase of the Néel temperature T N in weakly hole doped compounds. This increase of T N correlates with an increase of the resistivity. The analysis of our data strongly suggests that the hole mobility is the most important source for the strong suppression of antiferromagnetic order in La 2Ϫx Sr x CuO 4 . ͓S0163-1829͑99͒50102-1͔ RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
55
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 17 publications
8
55
0
Order By: Relevance
“…However, the mobility of the holes strongly enhances the effect of charge-carrier doping, what is also reflected in a much stronger suppression of T N by Sr doping as compared to Zn doping. 41 As shown in the lower panel of Fig. 4, the magnitude of κ mag for the various nominally undoped La 2 CuO 4 crystals varies by about a factor of two.…”
Section: Discussionmentioning
confidence: 86%
“…However, the mobility of the holes strongly enhances the effect of charge-carrier doping, what is also reflected in a much stronger suppression of T N by Sr doping as compared to Zn doping. 41 As shown in the lower panel of Fig. 4, the magnitude of κ mag for the various nominally undoped La 2 CuO 4 crystals varies by about a factor of two.…”
Section: Discussionmentioning
confidence: 86%
“…7 Study of the charge modulation has been become possible with the discovery that, for hole concentration of 1/8 per Cu atom, stripes can be pinned by the structural modulation induced by partial substitution of the ion Nd 3+ for La 3+ . 7 Recently, many experiments have been also provided evidence ( 63 Cu nuclear quadrupole resonance (NQR), 19 EXAFS, 20 x-ray, 21,22 muon-spinrotation (µSR) 23,24 and transport 22,25 measurements) for stripe correlations in pure or doped LSCO. Very recently, through neutron and x-ray diffraction and transport measurements on Nd-doped LSCO, it is showed that the charge stripes which order within the CuO 2 planes at low temperature are intrinsically metallic, contrary to what one would expect for conventional charge-density-wave (CDW) order.…”
Section: Stripesmentioning
confidence: 99%
“…In contrast, the effect of Cu dilution by nonmagnetic Zn is much weaker. Like in percolation, the AFLRO persists at Zn concentration, z, as large as 25 % [4].…”
mentioning
confidence: 99%
“…Recently, Hücker and coworkers [4] studied the phase diagram of La 2−x Sr x Cu 1−z Zn z O 4 , and found surprising results: It appears that the vacancies introduced by Zn doping weaken the destructive effect of holes (introduced by the Sr) on the AFLRO. E. g., in a sample with z = 15%, the critical concentration x c of the holes is approximately 3%, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation